2016
DOI: 10.1016/j.amjmed.2016.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death and Influencing Factors in Patients with Atrial Fibrillation

Abstract: The majority of deaths were related to a cardiovascular origin, and heart failure was the most common cause of death in atrial fibrillation patients. Despite the high risk of stroke associated with atrial fibrillation, only 7% died from stroke. Optimization of management of any underlying heart disease and associated comorbidities should be a relevant therapeutic target to reduce total mortality in atrial fibrillation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 34 publications
5
108
1
Order By: Relevance
“…Nevertheless, the association between atrial fibrillation and flutter and suicide was strengthened by the excess rate within the first 6 months and in combination with comorbid disorders. The high comorbidity linked to atrial fibrillation, for instance, in the form of heart failure and thromboembolic strokes , might contribute to the high rate; however, stroke was included in the comorbidity index used in the adjusted model. Other contributing factors could be the psychological distress associated with having a chronic disease and the continued symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the association between atrial fibrillation and flutter and suicide was strengthened by the excess rate within the first 6 months and in combination with comorbid disorders. The high comorbidity linked to atrial fibrillation, for instance, in the form of heart failure and thromboembolic strokes , might contribute to the high rate; however, stroke was included in the comorbidity index used in the adjusted model. Other contributing factors could be the psychological distress associated with having a chronic disease and the continued symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of death and CV death, even despite OAC use, has been highlighted in several previous studies [3,9,13,14]. AF patients may be progressively more clinically complex, due to the progressively increasing age and the higher prevalence of major CV diseases, partly explaining the increase in CV death.…”
Section: Multivariate Regression and Survival Analysesmentioning
confidence: 96%
“…Finally, there was a significant decrease in rates of both thromboembolic and major CV events, but a significant increase in all-cause and CV mortality.Both AF prevalence and incidence rise according to increasing age, and particularly in elderly and very elderly patients[1]. Importantly, increasing age increases morbidity and mortality in AF patients[12,13]. A similar analysis of trends in AF patients admitted to Medicare beneficiaries in USA, showed that from 1999 to 2013 there was a progressive increase in age and proportion of very elderly patients (age ≥85 years)[4].Proportionally, various comorbidities were increased among European AF patients.…”
mentioning
confidence: 91%
“…Fauchier et al [24] reported that among 8,962 patients with incident AF, majority of deaths during follow-up were related to cardiovascular disease (54%), and heart failure (29%) was specifically noted to be the most common cause of death. Notably, despite the high risk of stroke with AF, only 7% died from stroke [24]. GomezOutez et al [25] pooled data from 4 clinical trials representing 71,683 patients with AF.…”
Section: Discussionmentioning
confidence: 99%